Effectiveness of women leadership from the perspective of subordinates in institutions of higher learning in Klang Valley, Malaysia - Mohd, Harlina (2012)
The research was conducted to determine effective women leadership in the public and private institutions of higher learning in the Klang Valley from the perspective of the subordinates. Specifically, the study aims to examine the superior-subordinate communication and effective leadership of women Deans from public and private institutions of higher learning in terms of their upward communication and downward communication with their subordinates. It also sought to identify the relationship between specific demographic variables (gender, and highest academic qualification) and effective leadership of women leaders in public and private institutions of higher learning. Purposive sampling was used to identify faculties in the universities that having women as the Deans then a set of questionnaires were used as the instrument for data collection. A total of 467 respondents were picked through a simple random sampling procedure from the staff of five selected faculties of four institutions of higher learning in Klang Valley that have women as their Deans. A total of 393 completed questionnaires were returned, comprising 196 respondents from the public and 197 from the private institutions of higher learning, respectively. The data were analyzed using descriptive and inferential statistics such as the T-test and Pearson correlation. This study found that subordinates in the public and private institutions of higher learning agreed that the women Deans practised upward and downward communication in their daily communication with them. The result of the study, however, indicated that there was a significant difference between these two type of organizations. Public institutions of higher learning were rated as practising more upward comunication than downward communication. In the public institutions of higher learning, the upward communication variable contributed to the effective leadership. However, with the combination of both upward and downward communication, the women Deans were more effective in their leadership. Similarly, in the private institutions of higher learning, the upward communication variable increased the percentage of effective leadership of women Deans. When both upward and downward communiation are combined the leadership effectiveness of the women Deans increased. The study failed to accept the hypotheses of the relationship between specific demographic variables of gender, and highest academic qualification, and effective leadership of women leaders. The study has therefore contributed significantly to the understanding of Superior-subordinate communication and Leader-Member Exchange Theory.